Sequence analysis, purification, and study of inhibition by 4-quinolones of the DNA gyrase from Mycobacterium smegmatis. - Revel-Viravau, V (1996)
We determined the nucleotide sequence of a 6-kb DNA region harboring the recF, orf192, gyrB, and gyrA genes from Mycobacterium smegmatis mc(2)155. The amino acid sequences deduced from gyrA and gyrB displayed 89 and 86% identity, respectively, with the DNA gyrase from Mycobacterium tuberculosis, and 67 and 65% identity, respectively, with that from Streptomyces coelicolor. An open reading frame encoding the C-terminal region of the M. smegmatis RecF polypeptide was found upstream from gyrB and was 57% identical to the open reading frame encoding the C-terminal region of the S. coelicolor RecF protein. The gene orf192 was identified between recF and gyrB and was 39% identical to orf191 found in S. coelicolor in the recF-gyrB region. The M. smegmatis DNA gyrase, which was purified by affinity chromatography on novobiocin-Sepharose, consisted of two polypeptides with apparent molecular masses of 98 and 80 kDa. Determination of the N-terminal amino acid sequence of the B subunit confirmed GTG as the start codon in gyrB. Analysis of the supercoiling activity of the enzyme indicated that the M. smegmatis DNA gyrase was characterized by a specific activity equivalent to that of the Escherichia coli DNA gyrase. Inhibition of this activity by 4-quinolones was investigated by determining the 50% inhibitory concentrations (IC50S) of nalidixic acid, ofloxacin, and ciprofloxacin. The results indicated that the inhibitory activities of these drugs against the M. smegmatis DNA gyrase were markedly lower than those previously reported for the E. coli DNA gyrase. The results also suggested that the higher levels of activity of ofloxacin and ciprofloxacin against M. smegmatis (MICs, 0.5 to 1 microgram/ml), in contrast to that of nalidixic acid (MIC, 256 micrograms/ml), could be related to the higher inhibitory activities of fluoroquinolones against the DNA gyrase from this species (IC50S, 7 to 14 micrograms/ml) compared with that of nalidixic acid (IC50, 1,400 micrograms/ml).